2011
DOI: 10.1007/s10802-011-9597-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reciprocal Relations between Nonsuicidal Self-Injury, Negative Emotions and Relationship Problems in Chinese Adolescents: A Longitudinal Cross-Lag Study

Abstract: The present study explored the reciprocal relations between nonsuicidal self-injury (NSSI), negative emotions and relationship problems in a community sample of 2,435 (57.6% females) Chinese adolescents. Participants completed measures assessing 12 NSSI behaviors, three negative emotions (depression, anxiety and tension), and relationship problems at two time points over a 6-month period. A longitudinal cross-lag analysis was used to test the reciprocal relations among the studied variables. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 36 publications
4
49
3
5
Order By: Relevance
“…Despite these strengths, some limitations must be considered. First, this study was conducted in China, and relatively less research has classified NSSI in China (see You et al 2012;You et al 2011 for exceptions). It is possible that findings from this study are specific to Chinese adolescents and do not generalize to other cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these strengths, some limitations must be considered. First, this study was conducted in China, and relatively less research has classified NSSI in China (see You et al 2012;You et al 2011 for exceptions). It is possible that findings from this study are specific to Chinese adolescents and do not generalize to other cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies (e.g., Baetens et al 2013;Bureau et al 2010;Martin and Waite 1994), researchers report perceived lack of emotional support as a risk factor for NSSI in community-based samples of youth. You et al (2012) found that the perception of family invalidation (i.e., how children's emotional experience was invalidated by their parents) predicts the occurrence of NSSI 1 year later. Summarizing these results, international studies confirm the role of an invalidating environment in the development of NSSI.…”
Section: Associations Between Nssi and Family Factors In Adolescencementioning
confidence: 95%
“…Although we found that the link between emotional dysregulation and NSSI was robust across participants from various countries, such as the United States [42,51], Canada [59][60][61], Italy [52], Germany [55][56], New Zealand [62][63], and the Netherland [57], these countries are all western countries and participants in these studies were predominantly identified as Caucasian. Only two studies being reviewed involved non-western samples: one involved Turkish [38], and the other Japanese [64].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%